STUDENTS’ PERCEPTION OF USING NAPKIN AI-ASSISTED MIND MAPPING IN READING COMPREHENSION LEARNING - Verawati Mynjana; Sidik Indra Nugraha (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
Reading comprehension is an essential skill in English language learning; however, many students still experience difficulties in understanding texts, highlighting the need for innovative technology-assisted learning strategies. This study aims to explore students’ perceptions of using Napkin AI-assisted mind mapping in reading comprehension learning. This research employed a qualitative approach using observation and interviews conducted with eighth-grade students at SMP Islam At-Thohariyah. The participants consisted of six students selected purposively based on variations in reading ability. The findings revealed that most students had positive perceptions of using Napkin AI in reading activities. Students reported several benefits, including improved ability to identify main ideas, better comprehension of texts, and enhanced memory through visual mind mapping. In addition, the use of this technology increased students’ engagement and motivation in learning. However, some challenges were also identified, such as limited technological familiarity, the need for adaptation, and difficulties in selecting appropriate keywords. Overall, the study concludes that Napkin AI-assisted mind mapping has strong potential as an effective strategy in supporting reading comprehension learning, particularly in helping students organize information in a more structured and visual manner. ABSTRAK Kemampuan membaca pemahaman merupakan salah satu keterampilan penting dalam pembelajaran bahasa Inggris yang masih menjadi tantangan bagi banyak siswa, sehingga diperlukan strategi pembelajaran yang inovatif dan didukung teknologi. Penelitian ini bertujuan untuk mengeksplorasi persepsi siswa terhadap penggunaan mind mapping berbantuan Napkin AI dalam pembelajaran pemahaman membaca. Penelitian ini menggunakan pendekatan kualitatif dengan teknik observasi dan wawancara yang dilakukan pada siswa kelas VIII SMP Islam At-Thohariyah. Partisipan penelitian terdiri atas enam siswa yang dipilih secara purposive berdasarkan variasi kemampuan membaca. Hasil penelitian menunjukkan bahwa sebagian besar siswa memiliki persepsi positif terhadap penggunaan Napkin AI dalam kegiatan membaca. Siswa merasakan berbagai manfaat, seperti kemudahan dalam mengidentifikasi ide pokok, peningkatan pemahaman isi teks, serta kemudahan mengingat informasi melalui visualisasi mind map. Selain itu, penggunaan teknologi ini juga meningkatkan keterlibatan dan motivasi siswa dalam proses pembelajaran. Namun demikian, beberapa tantangan masih ditemukan, antara lain keterbatasan dalam penggunaan teknologi, kebutuhan waktu untuk beradaptasi, serta kesulitan dalam menentukan kata kunci yang sesuai. Secara keseluruhan, penelitian ini menyimpulkan bahwa mind mapping berbantuan Napkin AI memiliki potensi yang kuat sebagai strategi yang efektif dalam mendukung pembelajaran membaca pemahaman, khususnya dalam membantu siswa mengorganisasi informasi secara lebih terstruktur dan visual.